2020
DOI: 10.1038/s41598-020-59442-0
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth and Characterization of AlInN-Based Core-Shell Nanowire Light Emitting Diodes Operating in the Ultraviolet Spectrum

Abstract: We report on the demonstration of the first axial AlInN ultraviolet core-shell nanowire light-emitting diodes with highly stable emission in the UV wavelength range. During the epitaxial growth of AlInN layer, an AlInN shell is spontaneously formed, resulted in the reduced nonradiative recombination on nanowire surface. The AlInN nanowires exhibit high internal quantum efficiency of ~ 52% at room temperature for emission at 295nm. The peak emission wavelength can be varied from 290 nm to 355 nm by changing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Further, given the low cost of Si substrate, the majority of studies of group-III nitride nanowire UV LEDs are on Si substrate. These nanowire LED structures are primarily grown by MBE (through a spontaneous formation process, as afore-discussed), and predominantly with AlGaN ternary nanowires [25,36,37,51,[65][66][67][68][69]. The relatively longer history of investigating the MBE growth of AlGaN nanowires on Si, compared with the growth on other foreign substrates, has also made AlGaN nanowire UV LEDs on Si of better performance compared with devices on other foreign substrates, albeit with various limitations of using Si substrate (see Section 4).…”
Section: Algan Nanowire Uv Leds On Simentioning
confidence: 99%
“…Further, given the low cost of Si substrate, the majority of studies of group-III nitride nanowire UV LEDs are on Si substrate. These nanowire LED structures are primarily grown by MBE (through a spontaneous formation process, as afore-discussed), and predominantly with AlGaN ternary nanowires [25,36,37,51,[65][66][67][68][69]. The relatively longer history of investigating the MBE growth of AlGaN nanowires on Si, compared with the growth on other foreign substrates, has also made AlGaN nanowire UV LEDs on Si of better performance compared with devices on other foreign substrates, albeit with various limitations of using Si substrate (see Section 4).…”
Section: Algan Nanowire Uv Leds On Simentioning
confidence: 99%
“…The central wavelength of the devices was approximately 367.5 nm. Compared with that for blue microLEDs in previous studies, the peak wavelength of our devices shifted little with increases in current [8,[18][19][20]. A previous study reported that the junction temperature of a <40µm device could be kept constant when the injection current density is <1000 A/cm 2 [19].…”
Section: Typical L-i-v Characteristicsmentioning
confidence: 47%
“…Table 1 The physical properties of the AlGaN and AlInN alloy, x shows the concentration of Al and In in %. 23,31 Parameters Description Al The computed electron concentration in LED HII and LED HIV is improved in Fig. 3(a).…”
Section: Effect Of Thin P-alinn Eblmentioning
confidence: 99%
“…The AlInN alloy for UV LEDs recently reported by some research groups have shown remarkable results. [23][24][25] Inspired by these studies, we introduced AlInN thin EBL in our proposed UV LEDs. Our study is theoretical; however, we expect that the experimental implementation will not be difficult.…”
Section: Introductionmentioning
confidence: 99%